The Roles of Financial Threat, Social Support, Work Stress, and Mental Distress in Dairy Farmers’ Expectations of Injury - Furey, Emilia M.; O’Hora, Denis; McNamara, John; Kinsella, Stephen; Noone, Chris (Frontiers in Public Health, 2016)
Farming is dangerous, with fatalities among the highest in any occupation. Farmers often work alone, work long hours, with unreliable equipment in difficult weather conditions with hazardous chemicals and livestock. In addition, farmers make large financial commitments exposing them to high levels of financial risk. Exposure to such financial risk can give rise to subjective experiences of financial threat that are psychologically challenging. The current study attempted to characterize the role that financial threat plays in farm injuries. One hundred and twenty one dairy farmers completed a battery of questionnaires assessing financial threat, social support, depression, anxiety, farm job stress and health and safety beliefs. Mental distress directly predicted farmers’ expectations of injury and a direct effect of non-financial farm stress approached significance. Mental distress mediated significant indirect effects of farm stress and financial threat, and social support served to reduce distress. These findings support calls for interventions designed to reduce farm stress and financial threat and increase social support for farmers.